2014
DOI: 10.1037/abn0000002
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of persistent complex bereavement disorder in conjugally bereaved adults.

Abstract: Persistent complex bereavement disorder (PCBD) is a bereavement-specific syndrome characterized by prolonged and impairing grief. Most research on this syndrome rests on the traditional latent variable model whereby symptoms reflect an underlying entity. The network (or causal system) approach offers an alternative framework for understanding PCBD that does not suffer from limitations inherent in the latent entity approach. The network approach to psychopathology conceptualizes the relation between symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
209
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(231 citation statements)
references
References 63 publications
(90 reference statements)
16
209
4
2
Order By: Relevance
“…Network analysis examined the relationship between proposed symptoms of PCBD to isolate and identify the key symptoms central to the disorder (Robinaugh et al, 2014). The most highly correlated symptoms were found to be preoccupation, emotional pain, yearning and feeling that life is empty.…”
Section: Evidence For the Clinically Useful Symptom Structure Of Icd-mentioning
confidence: 99%
See 1 more Smart Citation
“…Network analysis examined the relationship between proposed symptoms of PCBD to isolate and identify the key symptoms central to the disorder (Robinaugh et al, 2014). The most highly correlated symptoms were found to be preoccupation, emotional pain, yearning and feeling that life is empty.…”
Section: Evidence For the Clinically Useful Symptom Structure Of Icd-mentioning
confidence: 99%
“…The symptoms of PGD are found to be distinct from often comorbid near neighbours such as depression, PTSD and separation anxiety (Boelen, van de Schoot, van den Hout, de Keijser, & van den Bout, 2010; Boelen, 2013). Several different statistical methods have been used to confirm the distinct nature of PGD, including confirmatory factor analysis (Boelen, van den Hout, & van den Bout, 2008), latent class analysis (Boelen, Reijntjes, J. Djelantik, & Smid, 2016) and network analysis (Robinaugh, LeBlanc, Vuletich, & McNally, 2014). In light of recent research (Cozza et al, 2016; Mauro et al, 2017), it should be noted that different results have been reported in terms of the diagnostic performance of the PGD-2009 criteria, presumably depending on the study population sample.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous literature (Costantini et al, 2015a;McNally et al, 2014), we relied on different types of network models to obtain a more comprehensive representation of factors related to remission from depression. First, we examined simple correlational patterns (i.e, association network).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, much of the early work applying network analysis to stress-related syndromes characterized them as potentially causal systems of interacting symptoms (e.g. PTSD in earthquake survivors, McNally et al, 2015; complicated grief following spousal bereavement, Robinaugh, LeBlanc, Vuletich, & McNally, 2014; Robinaugh, Millner, & McNally, 2016). …”
mentioning
confidence: 99%